"1960" L'Art en France 1957-1967. - Ceysson, Bernard; Serveau, Max; Maison de la Culture, Saint-Etienne (Saint-Etienne : Musée d'Art et d'Industrie, 1983)
Picasso, Pablo ; Klein, Yves ; Mahé de la Villeglé, Jacques ; Ben ; Rancillac ; Monory, Jacques ; Stampfli, Peter ; Sieff, Jean-Loup
"1960" L'Art en France 1957-1967, Musée d'Art et d'Industrie, Saint-Etienne, Maison de la Culture, Saint-Etienne, du 4 mars au 30 avril 1983
boek
Keywords: Frankrijk